Effect of cross-running polypropylene intradermal suture technique on keloid scar: a single-blind randomized controlled trial - Herman Yosef Limpat Wihastyoko; Edith Sumaregita Rinhastyanti; Arviansyah Arviansyah; Yudi Siswanto; Wilma Agustina; Elisabeth Prajanti Sintaningrum (Faculty of Medicine, Universitas Trisakti, 2026)
BACKGROUNDKeloids are abnormal scars that present a therapeutic challenge. Various treatment modalities have been developed, including surgical excision. While cross-running intradermal sutures were previously created using absorbable polyglycolic acid, this study introduces a modification using a non-absorbable material. Therefore, this study aimed to evaluate the effect of the cross-running polypropylene intradermal suture (CR-PIS) technique compared to the simple interrupted suture technique on keloid repair. METHODSThis was a randomized controlled trial with a post-test-only design involving 30 male and female keloid patients aged 20-50 years. Participants were randomized into the treatment group (n=15) and the control group (n=15). Wound assessment using the Vancouver Scar Scale (VSS), Manchester Scar Scale (MSS), and Patient and Observer Scar Assessment Scale (POSAS) was performed at 3, 6, and 9 months after surgery. Differences in VSS, MSS, and POSAS scores between the CR-PIS group and the simple knot group were analyzed using the Mann-Whitney U test. RESULTSStatistical analysis revealed a significant difference between the simple knot and CR-PIS groups (p<0.05). The median scores for each assessment (VSS, MSS, and POSAS) decreased significantly at 3, 6, and 9 months, with the control group's values being higher than those in the CR-PIS group (p<0.05). These results indicate that the control group developed moderate scars, whereas the treatment group exhibited good scars. CONCLUSIONSThe CR-PIS is more effective than the simple knot technique in improving keloid scars, as shown by changes in wound appearance, morphological function, topography, and patient and evaluator assessments.